EFEKTIFITAS BERCERITA DENGAN MEDIA WAYANG KARAKTER MODERN UNTUK MENINGKATKAN KETRAMPILAN BERBICARA ANAK USIA DINI - Solekah; Lina Putriyani (STKIP Subang, 2024)
This research aims to explore the potential of storytelling methods using wayang media in improving the speaking skills of young children. Children at this age are at a critical developmental stage where speaking ability becomes an important aspect in the development of language and communication skills. Traditional methods of learning are often not interesting enough for children, so innovative and engaging approaches are needed. Parents' busy lives trigger a lack of interaction and communication with children, so that children are left to play alone without any assistance or two-way communication. This causes obstacles to early childhood speaking skills. The results of the research show that the storytelling method using wayang characters significantly increases children's participation in conversations, enriches their vocabulary, and improves understanding of syntax so that children's speaking skills improve.